(untitled) (The Agriculturists, 2020)
Field and laboratory experiments were conducted at the Bangabandhu Sheikh MujiburRahman Agricultural University, Gazipur, during boro season of 2015-2016 to determine the response of rice crop (BU Dhan 2) to different plant densities under different fertilizer levels. The variety was grown with three fertilizer levels viz. recommended (57-10-8-7-0.9 kg NPKSZn ha-1), 50% higher (114-20- 16-14-1.8 kg NPKSZn ha-1) and 50% lower (28.5-5-4-3.5-0.45 kg NPKSZn ha-1) than recommended level and three plant spacing (20 cm x 25 cm, 20 cm x 20 cm and 20 cm x 15 cm) representing wider, standard and closer plant densities. Nutrient uptake of the variety was higher at higher level of fertilizer and closer plant spacing. The highest grain yield 5.18 t ha-1 of the variety was associated with the highest nutrient uptake under higher dose of fertilizer at closer plant spacing. This treatment combination also showed the highest nitrogen (86.53 kg ha-1), phosphorus (9.85 kg ha-1), potassium (103.9 kg ha-1), sulphur (12.27 kg ha-1) and zinc uptake (265.76 g ha-1) of the variety, although nutrient use efficiency was higher at lower fertilizer level under wider plant density. The Agriculturists 2020; 18(1) 31-41